Dreizehn Jahre Istanbul, 1937-1949 - Kraus, Fritz Rudolf, 1910-1991. (Leiden ; Boston, Massachusetts)
2 c. (1. c. xix, 906 s. ; 2. c. s. 909-1753)
Keywords: "The German Assyriologist Fritz Rudolf Kraus was an academic emigrant who was forced to leave Germany during the Nazi period. Kraus spent thirteen years in exile in Istanbul, where he was appointed cataloguer at the Archaeological Museum. During his exile he kept in touch with his family in Germany and with colleagues, in particular his former teacher, Benno Landsberger, who had moved to Ankara in 1935. The selection of his voluminous correspondence presented in this work is an important source for the history of both Turkey and Germany during the years 1937 to 1950." -- "Der deutsche Assyriologe Fritz Rudolf Kraus war ein Wissenschaftler, der Deutschland während der Nazizeit gezwungenermaßen verlassen musste. Kraus verbrachte 13 Jahre im Exil in Istanbul, wo er zum Katalogisierer im Archäologischen Museum ernannt wurde. Während seines Exils blieb er in Kontakt mit seiner Familie und den Kollegen in Deutschland, insbesondere mit seinem ehemaligen Lehrer, Benno Landsberger, der im Jahr 1935 nach Ankara emigrierte. Die in diesem Werk zusammengestellte Auswahl seiner umfangreichen Korrespondenz ist eine bedeutende Quelle für die Geschichte der Türkei und Deutschland in den Jahren 1937 bis 1950." --